Genomic changes during the evolution of the Coxiella genus along the parasitism-mutualism continuum - Santos-Garcia, Diego; Morel, Olivier; Henri, Hélène; El Filali, Adil; Buysse, Marie; Noël, Valérie; McCoy, Karen D.; Gottlieb, Yuval; Klasson, Lisa; Zenner, Lionel; Duron, Olivier; Vavre, Fabrice (Peer Community Journal)

(untitled)
The Coxiellaceae family is composed of five genera showing lifestyles ranging from free-living to symbiosis. Among them, Coxiella burnetii is a well-known pathogen causing Q fever in humans. This bacterium presents both intracellular (parasitic) and environmental (resistant) forms. Recently, several environmental Coxiella genomes have been reported, among which several have come from intracellular mutualistic symbionts of ticks, termed Coxiella-like endosymbionts. We sequenced two new Coxiella-LE genomes from Dermacentor marginatus (CLEDm) and Ornithodoros maritimus (CLEOmar) ticks, the latter belonging to the C. burnetii lineage. Using these newly sequenced Coxiella-LEs and 43 Coxiellaceae genomes, we conducted comparative genomic and phylogenomic analyses to increase our knowledge of C. burnetii pathogenicity and the emergence of Coxiella-LEs. Results highlight the probably parasitic nature of the common ancestor of the Coxiellaceae. Indeed, the virulence factor Dot/Icm T4 Secretion System is present in most, but not all, Coxiellaceae. Whereas it is part of a putative pathogenic island in C. burnetii, it has been entirely lost or inactivated in Coxiella-LEs, suggesting its importance in pathogenesis. Additionally, we found that a Sha/Mrp antiporter was laterally acquired in the C. burnetii lineage. This antiporter might be involved in alkali resistance and the development of the resistant form that is able to persist in the environment for long periods of time. The Sha operon is eroded or absent in Coxiella-LEs. Finally, we found that all Coxiella representatives produce B vitamins and co-factors indicating a pre-adaptation of Coxiella to mutualism with hematophagous arthropods. Accordingly, the ancestor of C. burnetii and Coxiella-LEs was likely a parasitic bacterium able to manipulate its host cell and to produce vitamins and co-factors for its own use.